IMPULSIVE BUYING GENERASI Z SEBAGAI KONSUMEN E-COMMERCE DITINJAU DARI THE BIG FIVE OF PERSONALITY - Tiara Prameswari Yulia Wijaya; Sutarto Wijono (Journal of Innovation Research and Knowledge, 2025)
The growth of e-commerce in the digital era has encouraged the emergence of impulsive buying behavior, particularly among Generation Z who are highly familiar with technology. A preliminary study through questionnaires with 30 respondents and interviews with 10 respondents indicated that individuals aged 18-22 years showed higher impulsivity compared to those aged 13-17 and 23-28 years. This research aims to examine differences in impulsive buying behavior among Generation Z as e-commerce consumers based on the Big Five Personality dimensions (Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to Experience). The study employed a quantitative approach with a comparative design. Sampling was conducted using quota sampling with 100 respondents aged 18-22 years residing in Salatiga, consisting of 77% female and 33% male participants. The instruments used were the Impulsive Buying Scale developed from Rook and Fisher’s theory and the Indonesian version of IPIP-BFM-50 (Akhtar & Azwar, 2018). Data were analyzed using the Kruskal-Wallis test. The findings revealed that only the Agreeableness dimension showed a significant difference in impulsive buying (p = 0.000 < 0.05), whereas Extraversion, Conscientiousness, Neuroticism, and Openness did not show significant differences (p > 0.05). These results indicate that individuals with low Agreeableness levels are more likely to engage in impulsive buying, while the other four personality dimensions did not produce meaningful differences